Albert Camus: «The Plague» - Frontera Izquierdo, Pedro (Razón y fe, 2021)
On the occasion of the great increase in sales of The Plague, a novel by Albert Camus, the impact of the philosophy of the absurd in the second half of the twentieth century is described. In response to an epidemic situation, the thoughts and actions of the novel’s fictional characters raise such topical issues as selfishness, solidarity, sacrifice, the presence or absence of God, earthly humanism, Christian humanism, and even sanctity. The characters of Tarrou, Fr. Paneloux and Doctor Rieux are so current that they make Camus our contemporary.